2009
DOI: 10.1177/002214650905000203
|View full text |Cite
|
Sign up to set email alerts
|

Social Capital and Health Inequality: Evidence from Taiwan

Abstract: Does social capital, resources embedded in social relationships, influence health? This research examines whether social capital impacts depressive symptoms and overall perceived health status over and above the effects of social support. Our analyses use unique data from the Taiwan Social Change Survey collected in 1997, and measures social capital and social support through two network instruments (the position generator and the name generator). Results replicate the effects of social support, as measured th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
111
2
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(120 citation statements)
references
References 37 publications
(29 reference statements)
4
111
2
1
Order By: Relevance
“…This instrument asks people about their network members" occupational positions and considers these positions as good indicators of the network resources. Position generators have already been used in health studies (Carpiano & Hystad, 2011;Moore et al, 2011;Song, 2011;Song & Lin, 2009). In this study, respondents were asked whether they know friends, relatives or acquaintances who have any of the jobs from a list of 11 occupations.…”
Section: Individual Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…This instrument asks people about their network members" occupational positions and considers these positions as good indicators of the network resources. Position generators have already been used in health studies (Carpiano & Hystad, 2011;Moore et al, 2011;Song, 2011;Song & Lin, 2009). In this study, respondents were asked whether they know friends, relatives or acquaintances who have any of the jobs from a list of 11 occupations.…”
Section: Individual Characteristicsmentioning
confidence: 99%
“…This school of social capital is rooted in the work of Bourdieu (1986) and Lin (2001) and is called the "network resources" approach (Ferlander, 2007). Although health studies using this approach are less numerous, they have shown that network resources are positively associated with self-rated health (Carpiano & Hystad, 2011;Moore et al, 2011;Song & Lin, 2009;Verhaeghe et al, 2012) and several mental health outcomes (Acock & Hurlbert, 1993;Haines et al, 2011;Song, 2011;Song & Lin, 2009;Webber & Huxley, 2007;).…”
Section: Introductionmentioning
confidence: 99%
“…Carpiano and Hystad (2011) already found that network social capital is positively associated with a sense of belonging. Secondly, network social capital may affect health through providing people access to job opportunities, decent housing, high-quality health care and other instrumental resources (Berkman and Glass, 2000;Song and Lin, 2009). Haines and her colleagues (2011) suggested that better access to instrumental resources is responsible for the negative association between the average educational level of network members and reporting depressive symptoms.…”
mentioning
confidence: 99%
“…The studies of Song and Lin (2009) and Haines and her colleagues (2011) used the name generator to measure social support. This instrument lists the names of a few network members by asking questions about actual social support interactions during a specific timeframe before the interview (e.g.…”
mentioning
confidence: 99%
See 1 more Smart Citation